Resilience and Coping Intervention with Children and Adolescents in At-Risk Neighborhoods. Issue 2 (3rd March 2016) - Allen, Sandra F.; Pfefferbaum, Betty; Nitiéma, Pascal; Pfefferbaum, Rose L.; Houston, J. Brian; McCarter, Grady S.; Gray, Shelley Ryan
ABSTRACT: This study evaluated the Resilience and Coping Intervention for Children (RCI), a group intervention to increase coping skills and resilience in children and adolescents. RCI was delivered to children and adolescents residing in five at-risk neighborhoods in a southern U.S. city. Children's and adolescents' self-report of coping strategies, strengths and difficulties with behaviors and emotions, and hope indicated decreased difficulties with behavior and emotions and increased feelings of hope postintervention. Parent report of difficulties with behavior and emotions revealed a significant decrease in children but not in adolescents. Mean scores for four coping dimensions increased, but the increase was not statistically significant.